LINK BETWEEN SOME VIRULNCE FACTORS GENES AND ANTIBACTERIAL RESISTANCE OF PSEUDOMONAS AERUGINOSA - Ibrahim, Aida H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The research was aimed to demonstrate the frequency of virulence factors genes (exoenzyme S and exotoxin A) and to express their relationship to antibacterial resistance among Pseudomonas aeruginosa isolated from patients suffering from otitis externa. The results were revealed that only twenty one (32%) out of 65 clinical ear swabs were Pseudomonas aeruginosa. According to PCR amplification, 18 (85.7%) bacterial isolates were expressed both toxins ( exoenzyme S and exotoxin A). The data get by real time experiments were revealed that the isolates were give higher percentage of resistance were seen against Ceftazidime (90.5%) and Gentamicin (88.5%).Only thirteen isolates (61,90%) of Multidrug resistance (MDR) –Pseudomonas aeruginosa isolates were detected, and two (9.5%) isolates were resist to all 8 classes of antibiotics and considered as PDR, and three (14.2%) bacterial isolates resist seven classes of antibiotics which considered as XDR.